The Teddy Bear's birthday surprise. (Montreal, Canada : Tormont Publication, 1992)
Tatty Ted celebrate his birthday but no one remembered his birthday. But when he gets up, he can hardly believe in his eyes.
Keywords: Birthdays -- Fiction; Bears -- Fiction; Children stories